Prognosis of asymptomatic intracranial stenosis in patients with transient ischemic attack and minor stroke - Hurford, R; Wolters, FJ; Li, L; Lau, KK; Küker, W; Rothwell, PM (American Medical Association, 2020)
IMPORTANCE Asymptomatic intracranial stenosis (ICS) is a frequent finding on imaging results, particularly in the assessment of acute stroke. Although the management of symptomatic ICS is informed by randomized trials, to our knowledge there are few data on the prevalence and prognosis of asymptomatic ICS in patients with stroke and transient ischemic attack (TIA). OBJECTIVE To study the age-specific prevalence and prognosis of asymptomatic ICS in a population-based cohort of patients with TIA and minor stroke. DESIGN, SETTING, AND PARTICIPANTS All patients (predominantly white) recruited to the Oxford Vascular Study (Oxfordshire, England) between March 1, 2011, and March 1, 2018, with TIA and minor ischemic stroke (National Institutes of Health Stroke Scale score, 3), irrespective of age, were included (n = 1579). We determined the age-specific prevalence of 50% or more asymptomatic ICS and the associated stroke risk by face-to-face follow-up to 2018 on standard medical treatment without stenting. EXPOSURES Patients underwent magnetic resonance angiography of the intracranial and cervicocranial arteries, computed tomography angiography if magnetic resonance angiography was contraindicated, or carotid/transcranial Doppler ultrasonography if computed tomography angiography was contraindicated. MAIN OUTCOMES AND MEASURES The primary outcomes were the prevalence and prognosis of asymptomatic ICS. RESULTS Of 1368 eligible patients (mean [SD] age, 69.2 [13.9] years; 700 men [51.2%]) with intracranial vascular imaging, 426 ICS were identified in 260 patients (19.0%): 58 (4.2%) with only symptomatic ICS, 155 (11.3%) with only asymptomatic ICS, and 47 (3.4%) with both. The prevalence of any asymptomatic ICS increased from 4.8% for patients younger than 70 years to 34.6% for patients 90 years or older (P for trend < .001; odds ratio per decade, 1.96; 95% CI, 1.69-2.27) and was greater than that of 50% or more asymptomatic carotid bifurcation stenosis (202 [14.8%] vs 105 patients [7.2%]; relative risk, 2.04; 95% CI, 1.63-2.55, P < .001). However, the 155 patients with only asymptomatic ICS had no increase in risk of ischemic stroke compared with those with no ICS (unadjusted HR, 1.03, 95% CI, 0.49-2.17), with 8 first recurrent events (5.2%) during 506 patient-years of follow-up and 3 in the territory of the ICS (annualized risk, 0.59%; 95% CI, 0.12-1.73). CONCLUSIONS AND RELEVANCE The prevalence of asymptomatic ICS increases with age in white patients with TIA and minor stroke and is greater than that of asymptomatic carotid stenosis, but asymptomatic ICS does not increase the short- or medium-term risk of distal recurrent ischemic stroke for patients receiving standard medical treatment.